Let's talk about death, dying, and what matters most to you in life: Pretest and piloting of a translated and adapted conversation game - Julia Jaschke; Sara Söling; Juliane Köberlein-Neu (PEC Innovation)
Objective: This study aimed to pretest and pilot the German version of the Hello conversation game (German: Hey du) to assess its comprehensibility and acceptability. Like the original, Hey du is designed as a low-threshold method to empower people of almost all ages and health conditions to engage in advance care planning (ACP), particularly targeting young/healthy people for whom there are currently few or no ACP programmes. Methods: The conversation game was systematically translated into German using the TRAPD process and cognitively pretested in 12 interviews. Subsequently, two observational studies were conducted: Hey du was used in 1) a nursing school (n = 16) and 2) with groups of family and friends (n = 50). After completing the game, participants were surveyed regarding the game's acceptability and comprehensibility. Results: The results of the cognitive pretest and the observational studies show that the conversation game was acceptable and comprehensible in both settings. Most of the participants (>92 %) reported that Hey du helped them come to terms with their own wishes and preferences for medical and nursing care and that they felt comfortable playing the game. Conclusion: Hey du has the potential to motivate and empower people to deal with ACP. Innovation: Hey du is the first scientifically supported gamification approach in Germany to introduce ACP to people for whom no systematic ACP programs exist. The game provides a safe forum for people of almost all ages and health conditions to discuss their values regarding life, death, dying and what matters most.